2020
DOI: 10.31234/osf.io/w9ygc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Science of Wisdom in a Polarized World: Knowns and Unknowns

Abstract: Interest in wisdom in the cognitive sciences, psychology, and education has been paralleled by conceptual confusions about its nature and assessment. To clarify these issues and promote consensus in the field, wisdom researchers met in Toronto in July of 2019, resolving disputes through discussion. Guided by a survey of scientists who study wisdom-related constructs, we established a common wisdom model, observing that empirical approaches to wisdom converge on the morally-grounded application of metacognition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(82 citation statements)
references
References 0 publications
2
80
0
Order By: Relevance
“…Participants’ videotaped advice was transcribed. Two strictly trained undergraduate students rated participants’ advice on three wisdom criteria: metacognitive humility (MH) (i.e., recognize uncertainty and one’s limitation of knowledge), metacognitive flexibility (MF) (i.e., consider a multitude of life contexts and influencing factors, then use different rules to solve the problem/provide different advice), and perspective taking (PT) (i.e., reason about the life dilemma from others’ perspectives), which are well-acknowledged criteria for measuring wisdom 12 , 14 , 18 , 60 . A recent study found that the wise advising score on these three criteria could predict clinical psychologists' assessment of the potential for suicide prevention 61 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants’ videotaped advice was transcribed. Two strictly trained undergraduate students rated participants’ advice on three wisdom criteria: metacognitive humility (MH) (i.e., recognize uncertainty and one’s limitation of knowledge), metacognitive flexibility (MF) (i.e., consider a multitude of life contexts and influencing factors, then use different rules to solve the problem/provide different advice), and perspective taking (PT) (i.e., reason about the life dilemma from others’ perspectives), which are well-acknowledged criteria for measuring wisdom 12 , 14 , 18 , 60 . A recent study found that the wise advising score on these three criteria could predict clinical psychologists' assessment of the potential for suicide prevention 61 .…”
Section: Methodsmentioning
confidence: 99%
“…Through the external behavior of advising, it is possible to gain insight into one’s wisdom. More specifically, affording flexible, context-sensitive advice reflects metacognitive humility, metacognitive flexibility, and perspective taking—three hallmarks of wisdom consistently defined by researches as "morally-grounded application of metacognition to reasoning and problem-solving" 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Grossmann et al 2020include "seeing through illusion and self-deception" as a function of perspectival metacognition in their Figure 3. I would argue, again, that seeing through illusion and self-deception requires emotional awareness, emotion regulation, and empathy (Kunzmann & Gl€ uck, 2019)-components that are not discussed by Grossmann et al (2020). (Interestingly, in their Figure 1-B shows equanimity as a major quality of wisdom when it comes to life challenges, but not as an important component of researchers' working definitions of wisdom.…”
Section: Wisdom In Real Life Vs Wisdom In the Labmentioning
confidence: 99%
“…Yet there are moments in my life-family conflicts, endless and useless meetings, interactions with difficult students-where I yell, slam doors, and curse (or at least would like to do so) and where I am neither wise nor act wisely. How is that possible, according to the common model of wisdom proposed by Grossmann et al (2020)?…”
mentioning
confidence: 99%
See 1 more Smart Citation